Resistencia del mortero hidráulico a cinco edades diferentes utilizando cinco tipos de cemento nacional - Chinchilla-Mora, Natalia-María (Instituto Tecnológico de Costa Rica, 2016)
This project shows a study on the results obtained by analyzing the behavior of the compressive strength of the hydraulic mortar at advanced ages (7, 14, 28, 56 and 90 days) using cement of national origin of type UG (two brands), UG-AR (two brands) and MP (a brand) and two kinds of fine aggregate (River and Quarry). Generated curves of resistance against age for each type of mixture, which currently do not exist in the country for which the Instituto Costarricense del Cemento y del Concreto (ICCYC) supports this idea since it is of national interest have real information according to the conditions in the country. The development of this project was an experimental design, design of several factors was used for each age in study, which is a means to reduce and control the variance of the experimental error in order to achieve greater accuracy, subsequently was the characterization of fine aggregates to meet their quality and make a comparison between them , then a statistical analysis was made to the data of the different mixtures (treatments) obtained in the compressive strength tests to know the behavior of the same, finally arose curves of compressive strength with their respective confidence intervals, with parameters appropriate to the national context and real. In addition, by means of the Tukey test data suggested the combination Quarry * Brand B - UG is the most optimal, with a range of resistance to the 90 days of 43,01 MPa to 48.83 MPa
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Mortero; Pecisión; Normas ASTM; Compresión; Cemento; Arena